2016
DOI: 10.1002/cncr.30338
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic optical contrast imaging as a novel modality for rapidly distinguishing head and neck squamous cell carcinoma from surrounding normal tissue

Abstract: This study demonstrates the feasibility of using DOCI to rapidly and accurately distinguish HNSCC from surrounding normal tissue. An analysis of DOCI images revealed microscopic characterization sufficient for tissue-type identification consistent with histology. Such an intraoperative tool would be transformative by allowing the rapid delineation of tumor tissue from nontumor tissue and thus maximizing the efficacy of resection and improving patient outcomes. Cancer 2017;123:879-86. © 2016 American Cancer Soc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
30
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(30 citation statements)
references
References 35 publications
0
30
0
Order By: Relevance
“…Previous work have demonstrated the initial concept and promising human ex vivo pilot study image results have been demonstrated from the DOCI system. 17,18 Several mathematical expressions have been formulated to describe the behavior of the DOCI system and how the contrast mechanism is interpreted. Non-ideal models and assumptions are also provided when the illumination source contains a first-order decay because the illumination source cannot be experimentally turned off instantaneously.…”
Section: Doci System Theory and Modelmentioning
confidence: 99%
“…Previous work have demonstrated the initial concept and promising human ex vivo pilot study image results have been demonstrated from the DOCI system. 17,18 Several mathematical expressions have been formulated to describe the behavior of the DOCI system and how the contrast mechanism is interpreted. Non-ideal models and assumptions are also provided when the illumination source contains a first-order decay because the illumination source cannot be experimentally turned off instantaneously.…”
Section: Doci System Theory and Modelmentioning
confidence: 99%
“…lifetime) is a fluorophore-specific characteristic that is not influenced by the local concentration of fluorophores, the optical path, the local excitation intensity, or the local fluorescence detection efficiency (which is not possible in autofluorescence imaging) [28]. The intrinsic contrast mechanism accessed by DOCI parallels fluorescence lifetime imaging microscopy (FLIM), in which the endogenous fluorophore lifetime of tissue is probed by illumination with a pulsed, long-wave ultraviolet light source [26]. In comparison to FLIM, DOCI produces pixel values that are proportional to the aggregate fluorophore of the probed tissue without the requirement of fitting acquired data to complex mathematical models through a unique image frame normalization scheme [26].…”
Section: Doci: Screening For Oral Cancermentioning
confidence: 99%
“…The intrinsic contrast mechanism accessed by DOCI parallels fluorescence lifetime imaging microscopy (FLIM), in which the endogenous fluorophore lifetime of tissue is probed by illumination with a pulsed, long-wave ultraviolet light source [26]. In comparison to FLIM, DOCI produces pixel values that are proportional to the aggregate fluorophore of the probed tissue without the requirement of fitting acquired data to complex mathematical models through a unique image frame normalization scheme [26]. The avoidance of mathematical complexity in calculations enables scalable mapping of fluorophore lifetimes over macroscopic (not microscopic) fields of view with high contrast to noise ratios in a relatively short time frame (<60 sec image acquisition time) with all pixels acquired simultaneously.…”
Section: Doci: Screening For Oral Cancermentioning
confidence: 99%
See 2 more Smart Citations